(untitled) (World Economics and Finance Bulletin, 2024)
The study aimed to validate the possibility of adopting the European Excellence Model EFQM 2020 in the North Oil Company/Kirkuk through a checklist to assess the availability and documentation of the model’s three criteria (direction, execution, and results) through its dimensions of (vision, purpose, strategy, and Organizational culture and leadership, stakeholder engagement, Creating Sustainable Value, driving performance and transformation, stakeholder perceptions, and strategic and operational performance). The research found that North Oil Company attained a very good result in applying and documenting the standards of the European Excellence Model EFQM 2020, as it obtained (504.7) points out of 1000 with a percentage of (52.6%) and is thus an institution recognized for excellence. It is recommended to defeat all the shortcomings in the model’s standards and dimensions, fill the gaps in the dimensions of “Creating Sustainable Value” and “impressions of stakeholders,” and then fill the gaps in the other dimensions.